STRATEGI PEMASARAN PRODUK PEMBIAYAAN ARRUM HAJI DI PT. PEGADAIAN SYARIAH CABANG JELUTUNG JAMBI - Addiarrahman Addiarrahman; Umi Toeba (Al Fiddhoh: Journal of Banking, Insurance, and Finance, 2023)
This research is based on the number of customers for Arrum Haji products which are not as many as other products issued by Pegadaian Syariah Cabang Jelutung Jambi. There were very few customers who used this product at the beginning of the interview. The problem in this study is what are the obstacles faced by Pegadaian Syariah Cabang Jelutung Jambi in marketing Arum Haji products and how is the marketing strategy of Arrum Haji products in increasing the number of customers. The marketing strategy at Pegadaian Syariah Cabang Jambi applies a marketing mix, namely product strategy, price strategy, place strategy, and promotion strategy. The price strategy and location strategy are good, because the price given by the pawnshop has been determined by the head office, while for the location strategy before the Pegadaian Syariah Cabang Jelutung Jambi was established, a survey was carried out first. However, the product strategy and promotion strategy are not good, because the Pegadaian Syariah Cabang Jelutung Jambi has not been maximal in introducing its products, as well as its marketing strategy, it is necessary to improve promotional strategies to increase the number of customers, for example socializing to the public.